PRO-KONTRA KEBIJAKAN SYARIAT ISLAM DI BUMI SERAMBI MEKKAH - Deni Setiawan; Zuly Qodir; Hasse Jubba (DIALEKTIKA, 2020)
The struggle of the people of Aceh to get the legitimacy of implementing Islamic law has been ongoing from the government of President Sukarno. Finally, this long cycle pays off with the enactment of Law Number 11 of 2006 concerning the Government of Aceh, which discusses the birth of Islamic Sharia Qanun. Instead, it experienced a lot of rejection after the implementation of the Islamic Sharia Qanun. Inversely related to the Aceh Qanun before it was passed which received support from the community. Since 2006, the pros and cons of implementing Sharia Syariah Qanun has been ongoing. The fundamental problem that must be sought for a solution is the attitude of the discriminatory implementers and Qanun material that is not comprehensive. This study will discuss the implementation of Islamic Sharia Qanun, as well as several factors that contribute to the emergence of the rejection of the application of Islamic Sharia Qanun. The output of this research is to provide government recommendations to resolve the issue of upholding the Islamic Sharia Qanun in Aceh.